Security+ guide to network security fundamentals - Ciampa, Mark D. (Course Technology, Cengage Learning, 2012)
Reflecting the latest developments from the information security field, best-selling Security+ Guide to Network Security Fundamentals, 4e provides the most current coverage available while thoroughly preparing readers for the CompTIA Security+ SY0-301 certification exam. Its comprehensive introduction to practical network and computer security covers all of the the new CompTIA Security+ exam objectives. Cutting-edge coverage of the new edition includes virtualization, mobile devices, and other trends, as well as new topics such as psychological approaches to social engineering attacks, Web application attacks, penetration testing, data loss prevention, cloud computing security, and application programming development security.